Information systems today - Jessup, Leonard M., 1961- (Pearson Education, 2006)
For the introductory or information systems course required of business majors. Information Systems Today, 2e, speaks directly to WHY IS MATTERS today by focusing just on what every business student needs to know about information systems. From the Back Cover: Contemporary and well written, this book serves as a good desk reference for business professionals who need to know about information systems. Chapter topics include database management, telecommunications, electronic commerce, information system ethics, security, and more. For systems analysts or general business professionals who need to know about information systems